Ulos Sebagai Simbol Berkat dalam Budaya Batak Toba dan Relevansinya bagi Gereja Katolik - Albertus B.A.H Situmorang; Iman Jaya Manik (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2023)
In every ethnic life, there are various ways in which humans can express their faith. The symbols contained in the customs help humans to concrete their faith. For the Batak people, ulos is a symbol that expresses who they believe in, while the mangulosi event is a sign of giving blessings, blessings, and prayers. Therefore, between Catholic culture and faith there are theological similarities and relationships, especially regarding blessings. The purpose of this paper is, that the author wants to explore the meaning of ulos as a symbol of blessing in the Toba Batak marriage and its relevance in the Catholic faith. Also, it provides an understanding of the use of ulos in marriage as one of the Batak ancestral heritages that are maintained and lived by the Toba Batak people until now. The type of research used by the author is qualitative research. While the research method used in this study is the phenomenological method. The result obtained is that ulos become a means of blessing that is used by Allah to bless his fellows. Therefore, ulos is very relevant to be used both in community life and in religious life